Factors influencing food insecurity rates: A county by county observation from 2017 in New Jersey. (30th September 2020) - Ignace, K; Souza, M; Borges, C
Abstract: This observational study aimed to investigate food insecurity prevalence for children under 18 in New Jersey using secondary data from 2017. Total food insecurity rates per county for children under 18 and all people were gathered from the NJ Department of Health. Age and Sex 5-year estimates for total population and children were collected from the US Census. The median income in the past 12 months from 2013-2017 was collected from the US Census in addition to family poverty status in the past 12 months from 2013-2017. Additional data was collected from the Social Capital Index. A bivariate analysis and a chi-square test revealed that nine independent variables were correlated to food insecurity prevalence by county in New Jersey among children under the age of 18. The significant variables were total food insecurity prevalence for all people in a county (p=.000), median income in the past 12 months in 2017 age-adjusted dollars (p=.000), percent of families below the poverty level (p=.000), county-level index (p=.000), family unity (p=.000), institutional health (p=.002), collective efficacy (p=.003), percent of adults over the age of 18 not covered under any type of health coverage (p=.006), and percent of families headed by a single parent (p=.000). Regarding the multivariate analysis, only two variables were still significant. Median income (p=.030) and poverty status (p=.007). These two variables are strongly associated with food insecurity prevalence among children under the age of 18. Health insurance status and household income are correlated with food insecurity. Food insecure children were more likely to live in areas with high deprivation and experience both individual-level poverty and neighborhood deprivation. Key messages: Median income and poverty status are strongly associated with food insecurity prevalence among children under the age of 18. Food insecure children were more likely to live in areas with high deprivation and experience both individual level poverty and neighborhood deprivation.